Steeplechase 101: a basic framework for coaching the event - Granato, D. (Techniques Magazine, 2018)
This article intended to be an overview of the annual planning process used to develop steelechasers. The system is used by steeplechasers at Adams State University, including 7 time NCAA Division II National Chamption, and 8:26 steeeplechaser Tabor Stevens, as well as 9 time NCAA Division II National Champion and 9:48 steeplechaser Alicia Nelson. While we will not be disussing specific workouts of these elite athletes much, we will outline a process that has proven effective and can be adopted by coaches of any athlete interested in competing in the event.